Formation of the personnel reserve of trade Union leaders as a method of career management - Yu. I. Slepchenko (Путеводитель предпринимателя, 2020)
The article deals with the factors of formation of the personnel reserve in the trade Union bodies, affecting the career planning of employees who have chosen this field of activity. It describes the professional and personal qualities (competencies) that allow an employee to successfully move up the hierarchical ladder in the field of trade Union activity.